Fatigue experiments and life predictions of notched C-Mn steel tubes. (April 2023) - Kumar Jena, Shreebanta; Gupta, Suneel K.; Arora, Punit; Chattopadhyay, J.
Highlights: Effects of peak strain amplitude and strain gradient on test fatigue life studied. Localized strain using FEA is compared with measured strain. Fatigue life predictions using equivalent strain/critical plane based models. Fatigue life assessment considers information at hole tip/characteristic distance. Abstract: Present work is aimed at performing fatigue tests on notched C-Mn steel tubes. Tests were conducted on different sizes of notches under remote axial strain-controlled conditions. Individual effects of peak equivalent strain amplitude and strain gradient are brought out on experimental fatigue life. The localized measured strains are compared with corresponding outcome of FE analyses. Fatigue life for notched specimens was predicted based on peak equivalent strain amplitude/existing critical plane model considering stress/strain information at peak/characteristic distance locations. The characteristic distance location with critical plane model and peak equivalent strain amplitude results in improved fatigue life predictions.